Life cycle of a guinea pig - Royston, Angela (Des Plaines, Ill. : Heinemann Interactive Library, 1998)
An introduction to the life cycle of a guinea pig from the time a tiny pup is born until, eight months later, it is fully grown and ready to start a family of its own.
Includes bibliographical references and index.
78173
Keywords: Guinea pigs -- Life cycles -- Juvenile literature; Guinea pigs